THE EFFECT OF THE RADEC LEARNING MODEL WITH RECIPROCAL TEACHING ON PARAGRAPH MAIN IDEA COMPREHENSION IN ELEMENTARY SCHOOLS - Dyah Nur Hidayatun Janah; Nugraheti Sismulyasih SB (Jurnal Cakrawala Pendas, 2026)
The ability to understand the main idea of a paragraph is an important skill in reading comprehension, but many elementary school students still have difficulty in identifying the main idea correctly. This study aimed to examine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) instructional model integrated with the Reciprocal Teaching strategy on students’ ability to identify the main ideas of paragraphs, as well as to describe students’ learning activities during the implementation of this instructional model. This study employed a quasi-experimental research method with a Nonequivalent Control Group Design. The population and sample consisted of 58 fourth-grade students from SDN 3 Kedungsuren and SDN Jerukgiling. Data were collected using tests and observation sheets. Data were analyzed using t-test and N-gain analysis. The results indicated that the RADEC model combined with Reciprocal Teaching had a significant effect on students’ ability to comprehend paragraph main ideas (sig. = 0.000 < 0.05). Furthermore, students’ learning activities in the experimental group were classified as active, whereas those in the control group were only moderately active. In conclusion, this study confirms that the RADEC model integrated with Reciprocal Teaching is effective in improving students’ understanding of paragraph main ideas and in fostering active student engagement during the learning process.